Pengukuran Tingkat Kesehatan Koperasi Syariah (Studi Kasus KPN Syariah Kemenag Tanah Datar) - Mira Wati; Nita Fitria; Muhammad Deni Putra; Meireza Putri (ILTIZAM Journal of Shariah Economics Research, 2021)
The health of the cooperative before and after the case of misuse of funds by the management of KPN Syariah Kemenag Tanah Datar is reviewed from the aspects of capital, quality of productive assets, management, efficiency, liquidity, cooperative identity, independence, and growth, as well as compliance with sharia principles. The research objective was to determine the health level of the KPN Syariah Kemenag Tanah Datar. The assessment of aspects is carried out using Simple Additive Weighting (SAW) based on Regulation of the Deputy for Supervision of the Ministry of Cooperatives and SMEs RI Number: 07/Per/Dep.6/IV/2016 by weighting all criteria and alternatives that produce the right reference value stated in the numbers 0 to 100. The conclusion is that the health level of the cooperative is in a fairly good position, there is no difference either before the case of misuse of funds or after the incident occurred